Equations to prescribe bicycle saddle height based on desired joint kinematics and bicycle geometry - Gatti, A. A.; Keir, P. J.; Noseworthy, M. D.; Beauchamp, M. K.; Maly, M.R (European Journal of Sport Science, 2022)
Overuse knee injuries are common in bicycling and are often attributed to poor bicycle-fit. Bicycle-fit for knee health focuses on setting saddle height to elicit a minimum knee flexion angle of 25-40°. Equations to predict saddle height include a single input, resulting in a likely suboptimal bicycle-fit. The purpose of this work was to develop an equation to predict saddle height from anthropometrics, bicycle geometry, and user-defined joint kinematics.